The Need for Love and a Sense of Belonging in the Character of Ash in the Film “Fantastic Mr. Fox” (Universitas Pendidikan Indonesia, 2025)
The animated film Fantastic Mr. Fox (2009), directed by Wes Anderson, tells the story of a heist carried out by Mr. Fox and his friend Kylie. The main focus of this study is the unfulfilled hierarchy of needs experienced by a character in Fantastic Mr. Fox. In the film, Ash feels humiliated because of his behavior, talent, and appearance. This study aims to identify how the character Ash fulfills his need for love and belonging. The research applies intrinsic elements such as character and characterization, plot, setting, and conflict, as well as the extrinsic element of Abraham Maslow’s hierarchy of needs. This is a qualitative study using a descriptive qualitative approach. The findings show that Ash’s problems are caused by his family, his surrounding environment, and feelings of jealousy. As a result, Ash attempts to overcome these issues by showing his talents and changing his bad habits.